ANALISIS PENGARUH PERSEPSI KUALITAS, CITRA MEREK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK HENKY GLASS & CRAFT DI SEMARANG - Imroatul Khasanah (Faculty of Economics and Business Diponegoro University, 2017)
This study aims to determine how big the influence of perceived quality, brand image, andpromotion of the purchasing decisions on Henky Glass & Craft product. Morever, thisresearch also aims to analyze the dominant factor that influence on purchasing decisions onHenky Glass & Craft product. This population in this study is customer Henky Glass & Craftproduct in Semarang. The sample on this study is 100 respondents and the techniques usenon probability sampling technique with approach of accidental sampling. Method that usedin this study is multiple linear regression. Simultaneously, the results shows that perceivedquality, brand image, and promotion variables the positive and significant effect onpurchasing decisions on Henky Glass & Craft product.Key words: perceived quality, brand image,promotion, purchasing decisions.